Effect of maleic hydrazide and waxing on ripening and quality of tomato fruit - H. Ahmed, Ikhlas; A. Abu-Goukh, Abu-Bakr (Gezira Journal of Agricultural Science; Vol 1 No 2 (2003), 2021)
The effect of postharvest treatment of maleic hydrazide (MH) and waxing on ripening and quality of 'Stain-B' and 'UC-82' tomato fruits at 20 ± I 0 C and 85-90% RH was evaluated during 2002/2003 season. Maleic hydrazide at 100, 250 and 500 ppm delayed fruit ripening by one to three days in both tomato cultivars. The higher the concentration; the more the delay in fruit ripening. Waxing in addition to MH treatment resulted in 1-2 days more delay in fruit ripening, compared to MH treatment alone. The effect of MH treatment and waxing in delaying fruit ripening was in retarded respiratory climacteric, delayed colour development and total soluble solids (TSS) accumulation, decreased fruit softening, titratable acidity, phenolic content and weight loss, and retained ascorbic acid content